Antioxidant and fermentation properties of aqueous solutions of dried algal products from the Boso Peninsula, Japan. (September 2017) - Takei, Moemi; Kuda, Takashi; Eda, Mika; Shikano, Ayane; Takahashi, Hajime; Kimura, Bon
Abstract: The mineral and saccharide contents, and antioxidant properties in aqueous extract solutions of eleven dried algal products obtained from the Boso Peninsula, Japan, were investigated. Potassium content was high in the brown alga Sargassum fusiforme . Polysaccharides content and viscosity were high in the red algae Gloiopeltis furcata, Chondrus ocellotus and C. elatus. Total phenolic compound content, 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging capacity, and Fe-reducing power were high in brown algae Eisenia bicyclis, S. fusiforme and the red alga Pyropia sp. Superoxide anion (O2 − ) radical-scavenging capacity was high in G. furcata, C. ocellotus, C. elatus and the green alga Monostroma nitidum. Lactobacillus plantarum strains isolated from the coast could ferment G. furcata, C. elatus and M. nitidum . The O2 − radical-scavenging capacities of the red algae were increased by fermentation. These results suggest that some macroalgal beach-cast brown algae without fermentation and red algae with fermentation can be utilized as natural resources for functional foods. Highlights: Aqueous extracted solution (AES) were prepared from drifted algae on the Boso Peninsula. Among them, brown algae AES have high DPPH radical-scavenging capacity. Red algae G. furcate and Chondrus spp. AES have high O2 − radical-scavenging capacity. L. plantarum isolated from the coast could ferment G. furcate and Chondrus spp. AES. O2 − radical-scavenging capacity of the red algae AESs increased by fermentation.